THE INFLUENCE OF BRAND IMAGE, TRUST, AND SERVICE QUALITY ON REVISIT INTENTION MEDIATED BY PATIENT SATISFACTION (CASE STUDY AT THE BHAYANGKARA HOSPITAL OF THE YOGYAKARTA SPECIAL REGION REGIONAL POLICE) - Ahmad Syakur Banafif; Kosasih; Rulia; Etty Sofia Mariati Asnar; Farida Yuliaty; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of Brand Image, trust, and service quality on patients’ revisit intention with patient satisfaction as a mediating variable at Bhayangkara Hospital, POLDA of the Special Region of Yogyakarta. The increasing competition among hospitals demands a comprehensive evaluation of the factors that shape patient loyalty. This research uses a quantitative approach with a survey method involving 250 patient respondents selected through purposive sampling. Data analysis was conducted using Partial Least Square (PLS) with SmartPLS 4 software. The findings show that Brand Image, trust, and service quality have a positive and significant effect on patient satisfaction and revisit intention. Patient satisfaction is also proven to mediate the relationship between the three independent variables and revisit intention, as indicated by p-values below 0.05. These results confirm that a positive hospital image, trust in the competence of medical staff, and superior service quality create a satisfying patient experience, thus encouraging revisit behavior. Theoretically, this study strengthens the conceptual model that satisfaction is a key element bridging patients’ perceptions and loyalty in the healthcare sector. Practically, the findings provide implications for hospital management to enhance the synergy between image management, trust-building, and service quality improvement to create sustainable patient satisfaction and retention.